2006
DOI: 10.15517/rbt.v54i4.3108
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic and acute preclinic toxicity and some pharmacological effects of the water extract from leaves of Petiveria alliacea (Phytolaccaceae)

Abstract: We tested the effects of the aqueous extract of Petiveria alliacea leaves on acute and sub-chronic toxicity, hematocrit and blood glucose level and intestinal motility of male albino NGP mice of 20 to 25 g mean weight. Treatments were in all cases doses of 1 000 and 2 000 mg/kg animal weight and a control treatment with 0.5 ml distilled water, using 10 animals per treatment and administered orally every day (5 days per week). Experimental periods were 18 and 70 days for acute and sub chronic toxicity, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
4
10
1
Order By: Relevance
“…It is important, however, to highlight that the contrasting glycaemic outcomes from our study versus that of Lores and Cires Pujol (14) may arise because of differences in sample preparation and conditions. The aqueous extract at 400 mg/kg caused a significant ele-vation of FBG (p ≤ 0.01); this effect was similar to a study by García-González et al (9). The study reported a hyperglycaemic effect of P alliacea in mice.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It is important, however, to highlight that the contrasting glycaemic outcomes from our study versus that of Lores and Cires Pujol (14) may arise because of differences in sample preparation and conditions. The aqueous extract at 400 mg/kg caused a significant ele-vation of FBG (p ≤ 0.01); this effect was similar to a study by García-González et al (9). The study reported a hyperglycaemic effect of P alliacea in mice.…”
Section: Discussionsupporting
confidence: 89%
“…The study reported a hyperglycaemic effect of P alliacea in mice. The results from García-González et al (9) and our work suggest that the aqueous extract of P alliacea has a hyperglycaemic profile in normoglycaemic mice and rats. A high sugar content of the extract at higher doses could explain the hyperglycaemia observed, however, further chemical analysis is required to confirm this.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In several regions of the world is popularly used as antispasms, diuretic and diaphoretic, being used as a weak infusion of the leaves or roots against hydropsy, arthritis, rheumatism, malaria, poor memory and to induce abortion (Mors et al, 2000). It also presents antinociceptive action (Gomes et al, 2005), and analgesic anti inflammatory (Lopes-Martins et al, 2002) and hypoglycemic (García-Gonzalez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%